2016
DOI: 10.5194/gmd-9-3699-2016
|View full text |Cite
|
Sign up to set email alerts
|

Ozone air quality simulations with WRF-Chem (v3.5.1) over Europe: model evaluation and chemical mechanism comparison

Abstract: We present an evaluation of the online regional model WRF-Chem over Europe with a focus on ground-level ozone (O-3) and nitrogen oxides (NOx). The model performance is evaluated for two chemical mechanisms, MOZART-4 and RADM2, for year-long simulations. Model-predicted surface meteorological variables (e.g., temperature, wind speed and direction) compared well overall with surface-based observations, consistent with other WRF studies. WRF-Chem simulations employing MOZART-4 as well as RADM2 chemistry were foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
80
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(97 citation statements)
references
References 66 publications
16
80
1
Order By: Relevance
“…Knote et al (2014) attributed the differences in pollutants concentrations between these mechanisms to the differences in the treatment of VOCs, since the rate constants for the basic O 3 production and loss reactions are similar. Hourly correlation coefficients for O 3 are low (less than 0.30) for all three mechanisms which is comparable to the findings of Mar et al (2016). In their study, summertime O 3 hourly correlation coefficients at the Ayia Marina station (AQ01) were close to 0.2.…”
Section: Main Gaseous Pollutantssupporting
confidence: 72%
See 3 more Smart Citations
“…Knote et al (2014) attributed the differences in pollutants concentrations between these mechanisms to the differences in the treatment of VOCs, since the rate constants for the basic O 3 production and loss reactions are similar. Hourly correlation coefficients for O 3 are low (less than 0.30) for all three mechanisms which is comparable to the findings of Mar et al (2016). In their study, summertime O 3 hourly correlation coefficients at the Ayia Marina station (AQ01) were close to 0.2.…”
Section: Main Gaseous Pollutantssupporting
confidence: 72%
“…During the second phase of the Air Quality Model Evaluation International Initiative (AQMEII), the majority of the modelling groups using the RMS and CM mechanisms with the WRF-Chem model also reported O 3 concentrations overestimation over the eastern Mediterranean (Im et al, 2015a). However, Mar et al (2016) reported an underestimation of about 5 ppbV on summertime O 3 concentrations WRF-Chem model using the RMS mechanism. Our sensitivity tests showed that high PM 2.5 concentrations affect the O 3 concentrations through the aerosolradiation feedbacks by altering the radiation budget and as a consequence, the photochemical activity and the concentration of secondary pollutants.…”
Section: Main Gaseous Pollutantsmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent study by Mar et al (2016) highlighted the dependence of WRF-Chem predicted ozone air quality (over Europe) on the chosen chemical mechanism. These results indicate the need for evaluating the effects of emission inventories and chemical mechanisms on the model performance using a network of stations across south Asia, which has not been carried out thus far.…”
mentioning
confidence: 99%